Final report preliminary multi centric trial of urinary antegen detection test (kates) for visceral leishmaniasis in Nepal. - Serchand,Jeevan Bahadur (2002)
SUMMARY: This rapid detection of parasitic antigens in body fluid including urine by immunological tests such as KAtex has been a valuable addition to clinical medicine. However,existing method of microscopic bone-marrow examination and immunological test for antigen -enzyme-linked immunosorbent assay (ELISA) test for visceral leishmaniasis antigen are difficult to perform in the field, and this has limited there in rural areas of endemic countries like Nepal. In this study we have tested 276 urine samples from visceral leishmaniasis patients from different endemic areas of Nepal. Sixty-seven patients (24.3%) were found KAtex positive. The clinical picture of these patients was compared with the KAtex test and additional laboratory findings, knowledge, attitude and behavior were assessed. High rate of KAtex positive (97.4%) was found in bone marrow confirmed patients with high degrees of sensitivity and specificity. Hence the study confirmed that the KAtex test is suitable for the confirmation of suspected cases in the field and hospital where bone-marrow facilities are limited or where there is a lack of trained manpower as well as microscopic diagnosis is not available. Key words: Rapid diagnostic test Urinary antigen, Visceral leishmaniasis, Nepal.